Penentuan Pengaruh Plasmolisis pada Sel Daun Rhoeo Discolor - Habib Zikri; Fina Mauliani Azijah; Herlita Aprilia; Ita Fitriyyah; Siti Saodatul Wijaya; Kamila Syahla K. (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
This article aims to observe the effect of hypertonic sucrose solution concentration on plasmolysis of epidermal cells of Rhoeo discolor leaves. Plasmolysis occurs when plant cells lose air due to the surrounding hypertonic solution, which causes the cytoplasm to shrink and the plasma membrane to detach from the cell wall. In this experiment, Rhoeo discolor leaves were immersed in sucrose solutions with different concentrations (0.14 M to 0.26 M) for 30 minutes, and the percentage of plasmolyzed cells was calculated. The results showed that the higher the sucrose concentration, the more cells underwent plasmolysis. At low concentrations (0.14 M and 0.16 M), plasmolysis occurred at a small percentage (1.77% to 7.25%), while at high concentrations (0.24 M to 0.26 M), the percentage of plasmolyzed cells increased significantly, reaching 3.03% at a concentration of 0.26 M at the 30th minute. In addition, prolonging the immersion time to 30 minutes caused a decrease in the number of plasmolyzed cells, indicating that osmotic equilibrium was reached after a certain time. Overall, this study confirms that hypertonic environmental concentration has a direct effect on plant cell plasmolysis, with the intensity increasing with higher environmental concentrations.